Accessibility and the choice of network investments in the London Underground - David M Levinson; David Giacomin; Antony Badsey-Ellis (Journal of Transport and Land Use)
In 1863, the Metropolitan Railway of what came to be known as the London Underground successfully opened as the world's first subway. Its high ridership spawned interest in additional links. Entrepreneurs secured funding and then proposed new lines to Parliament for approval, though only some were actually approved. While putative rail barons may have conducted some economic analysis, the final decision lay with Parliament, which did not have modern transportation, economic, or geographic analysis tools available. How good were the decisions that Parliament made in approving Underground lines? This paper explores the role accessibility played in the decision to approve or reject proposed early London Tube schemes. It finds that maximizing accessibility to population (highly correlated with revenue and ridership) per expenditure largely explains Parliamentary approvals and rejections.